Peran Brand Trust Memediasi Pengaruh Celebrity Endorse terhadap Purchase Intention Produk Sabun Pembersih Wajah Biore di Kota Denpasar - Komang Cintya Trisna Dewi; I Gst. Ngurah Jaya Agung Widagda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The marketing technique aims to use the widespread recognition and favorable reputation of celebrities to promote their desirability and appeal among customers, particularly within the cosmetics sector. Hence, a proficient marketing approach is vital in order to allure and maintain clients. This research aims to explain the role of brand trust in mediating the influence of celebrity endorsement on purchase intention. This research was conducted on Biore facial cleansing soap customers who live in Denpasar City. The research sample consisted of 120 respondents selected using a non-probability sampling method with purposive sampling technique. Data was collected through a questionnaire distributed online using Google Forms. Data analysis was carried out using descriptive analysis and inferential analysis with the help of SPSS 26 software. The results of this research show that celebrity endorsement has a positive and significant influence on brand trust and purchase intention. Apart from that, brand trust also has a positive and significant influence on purchase intention, and mediates the influence of celebrity endorsement on purchase intention for Biore facial cleansing soap products in Denpasar City. The implication of this research is to provide evidence about consumer behavior and the development of marketing management science, especially regarding how celebrity endorsement and brand trust can influence purchase intentions